PENGARUH JENIS KAKI PROSTETIK DAN POSTUR TUBUH AWAL KETIKA MELAKUKAN AKTIVITAS PENGANGKATAN BEBAN DALAM KONDISI BERDIRI DIAM TERHADAP KESTABILAN DAN AKTIVITAS OTOT PADA PENGGUNA KAKI PROSTETIK - Nada Nazhifa Budiman, Fathiyya
In Indonesia, there is a type of prosthetic leg that is commonly used by transfemoral amputee, but many users still complain that the knee joint bends suddenly so that their stability is disturbed and lower back pain occurs when using it. A researcher from the Bandung Institute of Technology (ITB) has created a new prosthetic leg design by adding a brake control mechanism to the knee joint. The brake control mechanism is thought to help users maintain stability and minimize muscle activity, especially when doing physical work, but the performance of the prosthetic leg has never been tested. The aim of this study was to test the type of prosthetic leg and lifting activities in static conditions on muscle activity and stability by looking at the Center of Pressure (COP) parameter value. The research was doing by experimental using Electromyography (EMG) and Force Plate. In addition, a subjective approach was taken by measuring the level of discomfort using the Borg CR10 scale and measuring the perception of stability to see the consistency of the measurement. Six men were participants in this research. They were asked to lift and move loads from a lower height to a higher height using two types of prosthetic legs, existing prosthetic legs and prototype prosthetic legs. The weight lifting movement is carried out in two conditions, when the initial body posture is 20° and when the initial body posture is 80°. The weight of the load moved is 9 kg. The results showed that the type of prosthetic leg had a significant effect on the activity of the erector spinae (ES), gastrocnemius medialis (GC) biceps femoris muscles, RMS COP A-P value and COP A-P speed (p-value < 0.05). Meanwhile, the initial body posture when lifting weights has a significant effect on erector spinae (ES) muscle activity and the interaction of these two factors has a significant effect on biceps femoris (BF) muscle activity and the RMS COP M-L value (p-value < 0.05). From the results, it can be seen that the prototype type of prosthetic leg provides the best performance in minimizing muscle activity. These results are supported by measuring the level of discomfort in the upper back, lower back, hips, knees, ankles, calves and thighs. Meanwhile, for stability, existing prosthetic leg have been proven to provide the best performance in maintaining stability. However, these results are inversely proportional to the results of measuring perceived stability. From the results of measuring perception of stability, it can be seen that participants have a preference for using prototype prosthetic legs when doing lifting activities in static conditions.